Development of Speech Practice Book for Students Speaking Skill at English Education Department of Ibrahimy University - Cindy Komariah; Dwi Nurhadiansyah Wicaksono; M. Hilmy Hidayatullah; Devi Purmayanti (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
To improve the quality of education and learning in learning speaking in the English Education Department. Consideration of the lack of confidence in students caused by not knowing how to perform appropriately and well to appear confident to improve their speaking skill is also supported by the existence of appropriate learning media and can facilitate both students and teachers in learning to speak. Therefore, researchers conducted research and development of Speech Practice book learning media namely “A Guide Speech Practice Book to Elevate Your Performance” The research aims to describe the design development and feasibility of the product. This type of research is Research and Development (R&D) which follows the procedure of Borg and Gall. Which includes ten stages and then simplified into five stages which include: need analysis, product development, expert validation, product try-out, and final product. After going through several stages, the product feasibility assessment was started based on the results of experts which included content experts and design expert. Based on validation from the content expert with an average value of 4.6 with a percentage of 92% with a very feasible category. The results of validation from design expert get an average value of 4.5 with a percentage of 90% with a very feasible category. Then the product validation results of student responses get a total score of 3064 with a percentage of 94.2% with a category very feasible. based on the results of research and field tests that have been described, it can be concluded that the speech practice book for students speaking skill at the English Education Department is very feasible to use for speaking learning.